2006
DOI: 10.1002/dvdy.20933
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic plexus contributes ganglion cells to the hindgut enteric nervous system

Abstract: The hindgut enteric nervous system (ENS) contains cells originating from vagal and sacral neural crest. In avians, the sacral crest gives rise to the nerve of Remak (NoR) and pelvic plexus. Whereas the NoR has been suggested to serve as the source of sacral crest-derived cells to the gut, the contribution of the pelvic ganglia is unknown. The purpose of this study was to test the hypothesis that the pelvic ganglia contribute ganglion cells to the hindgut ENS. We observed that the quail pelvic plexus develops f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…5). Given that thoracic crest will produce enteric neurons when transposed rostrally (32) and, more generally, that neural crest cells are not specified before migration (33,34), the restriction of the dual sympatho-enteric fate to the cervical and sacral levels of the trunk crest is likely to stem, less from cell-intrinsic fate restriction than from topological factors, such as the continuity of the peri-aortic and foregut mesenchymes at one end, and the contiguity of the pelvic ganglion-a "staging site" for the enteric sacral crest (30,35)-to the rectum at the other end.…”
Section: Discussionmentioning
confidence: 99%
“…5). Given that thoracic crest will produce enteric neurons when transposed rostrally (32) and, more generally, that neural crest cells are not specified before migration (33,34), the restriction of the dual sympatho-enteric fate to the cervical and sacral levels of the trunk crest is likely to stem, less from cell-intrinsic fate restriction than from topological factors, such as the continuity of the peri-aortic and foregut mesenchymes at one end, and the contiguity of the pelvic ganglion-a "staging site" for the enteric sacral crest (30,35)-to the rectum at the other end.…”
Section: Discussionmentioning
confidence: 99%
“…29,33 In quail-chick chimeric grafting studies, sacral NCCs were found within nerve fiber tracts derived from the nerve of Remak that penetrated the wall of the colorectum at the level of the myenteric plexus. 5,8,34 Therefore, the migration of sacral NCCs in the hindgut is likely to be under the guidance of nerve fibers extending from pelvic ganglia. In contrast, the formation of neuronal processes always lags behind the migration front of vagal NCCs in the hindgut (Young et al 35 ; our unpublished observations).…”
Section: Unique Migratory Behaviors Of Sacral Nccs Within the Hindgutmentioning
confidence: 99%
“…For Shh immunostaining, guts were fixed in Histochoice (EMS). Cryosections and wholemounts were stained using the primary antibodies listed in Table S1 as described (Nagy et al, 2007). Fluorescent secondary antibodies included Alexa Fluor 594 (goat anti-mouse IgG, IgM and IgG1), Alexa Fluor 488 goat anti-mouse IgG2a, and Alexa Fluor 546 goat anti-rabbit IgG (all Molecular Probes; 1:1000).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In the developing hindgut, vagal crest-derived cells join neural crest cells originating from the sacral level of the neural tube to form the ENS (Burns and Le Douarin, 1998;Nagy et al, 2007Nagy et al, , 2012. The ENS consists of two ganglionated plexuses, myenteric and submucosal, which are composed of multiple types of neurons and glia arranged as concentric rings and are responsible for regulating the function of the gut, including peristalsis.…”
Section: Introductionmentioning
confidence: 99%